2019
DOI: 10.1007/s12576-019-00660-1
|View full text |Cite
|
Sign up to set email alerts
|

Different doses of methamphetamine alter long-term potentiation, level of BDNF and neuronal apoptosis in the hippocampus of reinstated rats

Abstract: Methamphetamine (METH) is a psychostimulant. The precise mechanisms of its effects remain unknown and current relapse treatments have low efficacy. However, brain-derived neurotrophic factor (BDNF) and neuronal plasticity are essential contributors, despite paradoxical reports and a lack of comprehensive studies. Therefore, we investigated the effects of different doses of METH on long-term potentiation (LTP), BDNF expression and neuronal apoptosis in the hippocampus of reinstated rats. Rats were injected intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 75 publications
1
16
0
Order By: Relevance
“…In this study we observed that gp120, when applied alone, attenuated hippocampal LTP, which is consistent with the findings that gp120 inhibited short- and long-term potentiation in the hippocampus when applied acutely onto the hippocampal slices ( Dong and Xiong, 2006 ; Shen et al, 2015 ), administered to the brain via intracerebroventricular infusion (for 3–5 days) ( Sanchez-Alavez et al, 2000 ), or overexpressed in the brain in gp120-transgenic animals ( Hoefer et al, 2015 ; Krucker et al, 1998 ). We also observed that Meth reduced LTP when applied acutely, which is in agreement with the results that Meth reduced LTP recorded either in the CA1 region of mouse hippocampus in vitro ( Swant et al, 2010 ) and rat hippocampus ex vivo ( Hori et al, 2010 ; Onaivi et al, 2002 ) or in the dentate gyrus in vivo in reinstated rats ( Shahidi et al, 2019 ), along with the findings observed in the medial portion of the prefrontal cortex ( Ishikawa et al, 2005 ) and in the cortical-striatal region of rats with self-administration of Meth ( Huang et al, 2017 ). In addition to its suppressive effect, Meth was also found, when administered for a long-term with a low dose, to enhance LTP in differentiating and mature mouse dentate gyrus neural cells ( Baptista et al, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…In this study we observed that gp120, when applied alone, attenuated hippocampal LTP, which is consistent with the findings that gp120 inhibited short- and long-term potentiation in the hippocampus when applied acutely onto the hippocampal slices ( Dong and Xiong, 2006 ; Shen et al, 2015 ), administered to the brain via intracerebroventricular infusion (for 3–5 days) ( Sanchez-Alavez et al, 2000 ), or overexpressed in the brain in gp120-transgenic animals ( Hoefer et al, 2015 ; Krucker et al, 1998 ). We also observed that Meth reduced LTP when applied acutely, which is in agreement with the results that Meth reduced LTP recorded either in the CA1 region of mouse hippocampus in vitro ( Swant et al, 2010 ) and rat hippocampus ex vivo ( Hori et al, 2010 ; Onaivi et al, 2002 ) or in the dentate gyrus in vivo in reinstated rats ( Shahidi et al, 2019 ), along with the findings observed in the medial portion of the prefrontal cortex ( Ishikawa et al, 2005 ) and in the cortical-striatal region of rats with self-administration of Meth ( Huang et al, 2017 ). In addition to its suppressive effect, Meth was also found, when administered for a long-term with a low dose, to enhance LTP in differentiating and mature mouse dentate gyrus neural cells ( Baptista et al, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…Accumulating evidence indicates that addictive drugs hijack the striatal memory systems to produce the behavioral effects [ 24 ]. Accordingly, methamphetamine exposure has been shown to alter synaptic plasticity in multiple neuronal systems of the reward circuitry, including the striatum [ 15 , 48 , 49 , 50 , 51 , 52 , 53 ]. Synaptic adaptations in the dorsal striatum underlie habit learning [ 54 ] and escalation of methamphetamine self-administration-induced altered plasticity in the dorsal striatum might therefore play a role in enhancing vulnerability to methamphetamine addiction [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, fluoxetine treatment increased synaptic plasticity and dendritic spine remodeling induced the growth of cerebrocortical synapses (Rubio et al, 2013). LTP, as a form of synaptic plasticity, has been regarded as a critical cellular mechanism underlying learning and memory (Shahidi et al, 2019a).…”
Section: Discussionmentioning
confidence: 99%